Convergent total synthesis of corallocin A. Issue 23 (21st May 2021) - Mashiko, Tomoya; Nakazato, Yuta; Katsumura, Yuta; Kasamatsu, Akihiko; Adachi, Shinya; Kamo, Shogo; Matsuzawa, Akinobu; Sugita, Kazuyuki
Abstract : The first total synthesis of corallocin A was archieved via Suzuki coupling and other key reactions. Abstract : The first total synthesis of corallocin A is described herein. The Suzuki coupling reaction as a key step proceeded with high stereoselectivity and in good yield. Robust transformations, including Vilsmeier–Haack formylation and Wittig reaction, allowed for effective access to corallocin A.